Active Learning Materials for English Online Classes Based on Genre-Based Approach - Amira Deani; Dwiyanto Djoko Pranowo (STAI Hubbulwathan Duri, 2022)
The COVID-19 pandemic has impacted all aspects, including education. This phenomenon has drastically changed the teaching and learning interactions in schools. This change shocked teachers and students unprepared for competence, subject matter, and technology, including psychology. For that constraint, the authors are interested in contributing their ideas/thoughts in the form of developing active learning materials for English online classes based on a genre-based approach for VIII grade junior high school students. The researchers developed the product through development research (RD) involving a sample of 114 VIII grade junior high school students and 3 English teachers. Through needs analysis of respondents, researchers can map the objectives and learning materials needed by respondents. Researchers use this need analysis to develop online-based learning materials. The final product is a supplementary online book consisting of 6 units with different themes. From the results of field trials, it is known that this book is very well received by the user, in this case, the VIII grade students and English teachers of SMP/MTs.